Walk 11 AT A GROVE - -, - (project baikal, 2012)
Zvezdochka GroveLomonosov School in IrkutskSt Vladimir SchoolThe Residential Complex “Zavidnyi”“Mebel.RU” Store on Gogol StreetSchool № 80 on Pushkin Street